Central and peripheral hemodynamics in exercising humans: leg vs arm exercise. (December 2015) - Calbet, J. A. L.; González‐Alonso, J.; Helge, J. W.; Søndergaard, H.; Munch‐Andersen, T.; Saltin, B.; Boushel, R.
Abstract : In humans, arm exercise is known to elicit larger increases in arterial blood pressure (BP) than leg exercise. However, the precise regulation of regional vascular conductances (VC) for the distribution of cardiac output with exercise intensity remains unknown. Hemodynamic responses were assessed during incremental upright arm cranking (AC) and leg pedalling (LP) to exhaustion (Wmax ) in nine males. Systemic VC, peak cardiac output (Qpeak ) (indocyanine green) and stroke volume (SV) were 18%, 23%, and 20% lower during AC than LP. The mean BP, the rate‐pressure product and the associated myocardial oxygen demand were 22%, 12%, and 14% higher, respectively, during maximal AC than LP. Trunk VC was reduced to similar values at Wmax . At Wmax, muscle mass‐normalized VC and fractional O2 extraction were lower in the arm than the leg muscles. However, this was compensated for during AC by raising perfusion pressure to increase O2 delivery, allowing a similar peak VO2 per kg of muscle mass in both extremities. In summary, despite a lower Qpeak during arm cranking the cardiovascular strain is much higher than during leg pedalling. The adjustments of regional conductances during incremental exercise to exhaustion depend mostly on the relative intensity of exercise and are limb‐specific.